GENETIC DIVERSITY OF DRUG RESISTANT STRAINS OF MYCOBACTERIUM TUBERCULOSIS IN OMSK REGION - O. A. Pаsechnik; M. A. Dymovа; V. L. Stаsenko; M. P. Tаtаrintsevа; I. P. Kolesnikovа; E. S. Lyapinа (Туберкулез и болезни лёгких, 2017)
The article presents the investigation results of the specific epidemic situation on tuberculous infection in Omsk Region in 2006-2015 and molecular genetic features of M. tuberculosis strains with multiple drug resistance circulating in this region. Bacteriological, molecular genetic methods, VNTR-typing were used as well as descriptive techniques of the epidemiological process. Tuberculosis prevalence made 269.2 per 100,000 population. There is an increase in those with bacillary excretion among new cases of respiratory tuberculosis from 39.8% to 53.4%. Drug resistance was detected in 48.0% of new cases. Among drug resistance patterns, MDR made 57%, and extensive drug resistance (XDR) increased from 2.5 to 7.0%. In 2015 prevalence of XDR tuberculosis made 8.9 per 100,000 population in Omsk Region. When performing VNTR-typing of 77 samples of M. tuberculosis DNA with MDR, 27 genetic types were identified. The population of MDR strain of M. tuberculosis is heterogeneous and presented by strains of various genetic families -Beijing, LAM, S,Haarlem,Uganda. The investigation showed that isolates ofBeijing family prevailed (76.6%).